(untitled) (Sociología y tecnociencia, 2024)
Attitude is a significant factor in the formation of violent conflict. Therefore, efforts to change hostile attitudes into peaceful ones are vital to the success of peacebuilding in countries emerging from conflict. Peace media has become an important weapon for influencing people’s opinions in order to remove the cultural violence that has gotten entrenched during the conflict and replace it with a culture of peace. Using securitization theory, the purpose of this study is to explain how peace media utilized desecuritization to turn warring sentiments into peace attitudes in Aceh following the 2005 Helsinki Memorandum of Understanding (MoU) promoting peace. This study reveals that Tribune Aceh, Kompas, and Republika have emerged as key participants in the desecuritization of the Aceh conflict, allowing them to promote a peaceful mindset among the public. Despite the difficulties associated with the Helsinki MoU’s implementation, the completion of this desecuritization eventually contributed to the development of permanent peace in Aceh.